PSYCHOLOGICAL ASPECTS OF FORMATION OF A PRACTICE-ORIENTED ENVIRONMENT IN EDUCATIONAL INSTITUTIONS OF THE MINISTRY OF INTERNAL AFFAIRS OF RUSSIA - O. A. Ulyanina (Russian State Vocational Pedagogical University, 2018)
Introduction. Modernisation of the Russian higher education system, change of conceptual paradigm and transition to competency-based approach to specialist training, which meets the urgent needs of informational technological society, make it necessary to study and develop methodological, content and procedural aspects of the implementation of this approach in practice.The aim of the research was to study psychological and pedagogical features of the design of a practice-oriented environment, contributing to the formation of personal competency of cadets of educational institutions of the Ministry of Internal Affairs of Russia.Methodology and research methods. The methodological framework of the research was based on comparative analysis, synthesis and generalisation of the content of the Russian and foreign publications, which describe the theory and practice of environmental and competency-based approaches in higher education.Results and scientific novelty. The peculiarities of the implementation of the environmental approach to the training of future specialists were shown. The con tent and conceptual meaning of such categorical-conceptual units concerning "environment" and "educational environment" was defined. The category of practice and its varieties in educational institution was analysed. The specificity of practice-oriented environment of educational organisations of the Ministry of Internal Affairs of Russia was described. The importance of practical orientation of educational environment as a prerequisite for cadets' education was shown. The criteria of efficiency of the practice-oriented environment were distinguished. The final purposes of education were formulated, including personal competency of future specialists as the main purpose of education. The author emphasises the significance of a complex programme realisation for cadets' psychological support as an integral component of practice-oriented educational environment of ministerial higher education institutions. The following main blocks of the program were highlighted and characterised: target, deterministic, content, medium, technological, analytically monitored, organisational and procedural. On the basis of the allocated blocks and their substantial description the attention is focused on advantages of implementation of this program promoting continuous personal improvement and realization of potential of participants of educational process.Practical significance. The author is convinced that the implementation of a comprehensive programme of psychological support in educational establishments of the Ministry of Internal Affairs of Russia will contribute to the continuous personal development and realisation of students' potential and, ultimately, will improve the efficiency of vocational education of graduates.